Peran Teman Sebaya dalam Mengembangkan Kemampuan Berbahasa dan Berbicara Anak Usia Dini di Sekolah Inklusi - Dwi Jayanti, Diana (ACIECE, 2019)
This is a qualitative of a case study aimed at knowing and describe the involvement of peers in developing the ability to speak and speak early children in inclusive schools. The subjects in this study were chosen through the procedure of determining the subjects in qualitative research proposed by Sarantakos (1993, in Poerwandari 2005), namely: 1) not directed to the large number of participants but in typical cases according to the specificity of the research problem, 2) not directed to representation in terms of numbers or random events, but to context matches. Data collection methods are through observation, interviews, and informal assessments, as well as field notes documentation. Data analysis is performed by comparing the initial condition of subjects before being stimulated with the initial condition of the subjects after stimulation is performed. This study showed that peer involvement in the process of stimulating the development of language skills and speaking of the subject gives a fairly positive influence interms of: 1) giving positive encouragement and motivation to the subject to be able to learn to imitate the pronunciation of the right friend and correct the pronunciation of the less precise words he said, 2) increasing the subject's confidence and self-acceptance so as not to be afraid of being wrong and encourage the subject to be able to try to express themselves more verbally through words